2021
DOI: 10.3389/fonc.2021.645623
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Neuroendocrine Neoplasms Overexpressing Epithelial-Mesenchymal Transition Mechanical Barriers Genes Lack Immune-Suppressive Response and Present an Increased Risk of Metastasis

Abstract: Typical carcinoids (TC), atypical carcinoids (AC), large cell neuroendocrine carcinomas (LCNEC), and small cell lung carcinomas (SCLC) encompass a bimodal spectrum of metastatic tumors with morphological, histological and histogenesis differences, The hierarchical structure reveals high cohesiveness between neoplastic cells by mechanical desmosomes barrier assembly in carcinoid tumors and LCNEC, while SCLC does not present an organoid arrangement in morphology, the neoplastic cells are less cohesive. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
(69 reference statements)
1
10
0
Order By: Relevance
“…The tumor samples were enriched for earlier stages (I/II) in carcinoid tumors according to the 8th edition of the International Union for Cancer Control (UICC) TNM Classification of Malignant Tumors [ 1 ] and consisted of primary lung tumors obtained by surgical resection. The TC and AC cases were selected to obtain a balanced number of cases in each group, as in our previous study [ 12 ]. The cohort comprises 5 TC, 5 AC, 4 LCNEC, and 10 SCLC according to the current World Health Organization (WHO) 2021 classification [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tumor samples were enriched for earlier stages (I/II) in carcinoid tumors according to the 8th edition of the International Union for Cancer Control (UICC) TNM Classification of Malignant Tumors [ 1 ] and consisted of primary lung tumors obtained by surgical resection. The TC and AC cases were selected to obtain a balanced number of cases in each group, as in our previous study [ 12 ]. The cohort comprises 5 TC, 5 AC, 4 LCNEC, and 10 SCLC according to the current World Health Organization (WHO) 2021 classification [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ct_HKG)]. The studied genes that were differently expressed (DEG) were obtained from a panel of 84 EMT genes, the same platform that was applied in a previous study by our group (GSE181381) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be assumed that STEAP1 may play a similar role in PI3K-Akt signaling pathway. Acting as EMT transcription factors, EGFR and STEAP1 were proved to be highly expressed among pulmonary neuroendocrine carcinomas and downregulated in carcinoid tumors [ 44 ], which suggested that STEAP1 may have interaction with EGFR pathway in the process of EMT. However, there are few studies about STEAP1 and HGFR or integrin-mediated signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study implicated the upregulation of EMT transcription factors (BMP1, CDH2, KRT14, etc.) to high proliferation rates, mechanical molecular barriers disassembly, and increased cancer cell motility, leading to metastasis risk in pulmonary neuroendocrine neoplasms [ 15 ]. BMP1 is a potential biomarker and mediator in diversified malignant tumors, whereas the function and pathway of its impact on pancancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%